Effects of individualized versus traditional power training on strength, power, jump performances, and body composition in young male nordic athletes - Prieske, O.; Chaabene, H.; Kullmann, N.; Granacher, U. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This study aimed to examine the effects of individualized-load power training (IPT) versus traditional moderate-load power training (TPT) on strength, power, jump performance, and body composition in elite young Nordic athletes.